Influence of Hydrodistillation Conditions on Yield and Composition of Coriander (Coriandrum sativum L.) Essential Oil - Huzar Elżbieta; Dzięcioł Małgorzata; Wodnicka Alicja; Örün Harun; İçöz Arda; Çiçek Erkan (Polish Journal of Food and Nutrition Sciences)
The yield and composition of essential oil obtained from the fruits of coriander (Coriandrum sativum L.) cultivated in Poland were investigated. Experiments were carried out by means of the hydrodistillation method using Clevenger and Deryng apparatus. No effect of the apparatus' construction on the essential oil yield was observed during a 2-h process (yield of 1.62%). The composition of the coriander essential oil was determined by using gas chromatography with mass spectrometry (GC-MS). The main components were linalool (78.45%), α-pinene (5.03%), camphor (3.90%), γ-terpinene (3.80%), D-limonene (2.58%) and geranyl acetate (2.13%). Moreover, the influence of different factors, such as time of hydrodistillation, sodium chloride addition and method modification by using microwave heating on essential oil yield, was studied. The addition of sodium chloride to distilled water did not affect the yield of essential oil, but slightly increased the content of camphor. Replacing conventional heating with microwaves during 15-min experiments enhanced the yield of essential oil from 1.20 to 1.35% and had a slightly greater influence on its composition, increasing the contents of some less volatile components: linalool, camphor, geraniol, p-cymene and D-limonene. The results obtained indicate that microwave heating may be a supporting method for the production of coriander essential oil using the hydrodistillation process.